Design and Fabrication of Small Vertical-Take-Off-Landing Unmanned Aerial Vehicle - Abd Rahman Yasir Ashraf (MATEC Web of Conferences, 2018)
Modern UAVs available in the market have well-developed to cater to the countless field of application. UAVs have their own limitations in terms of flight range and manoeuvrability. The traditional fixed-wing UAVs can fly for long distance but require runways or wide-open spaces for take-off and landing. On the other hand, the more trending multirotor UAVs are extremely manoeuvrable but cannot be used for long-distance flights because of their slower speeds and relatively higher consumption of energy. This study proposed the implementation of hybrid VTOL UAV which has the manoeuvring advantage of a multirotor UAV while having the ability to travel fast to reach a further distance. The design methodology and fabrication method are discussed extensively which would be followed by a number of flight tests to prove the concept. The proposed UAV would be equipped with quadcopter motors and a horizontal thrust motor for vertical and horizontal flight modes respectively.